Implementation of Internal Quality Assurance System in Improving the Quality of Education - Nurmarito Rambe; Amiruddin Siahaan; Inom Nasution (SAINTIS Publishing, 2025)
This research aimed to analyze the implementation of the Internal Quality Assurance System (SPMI) in improving the quality of education at MAN 2 Model Medan. Using a qualitative approach and semi-structured interviews, data were collected from five participants consisting of the principal, vice principal, quality assurance team leader, teaching staff, and administrative personnel. The data were analyzed using thematic analysis and critical discourse analysis to explore the participants' experiences in planning, implementing, and evaluating the quality system based on the Operational Curriculum of Madrasah (KOM). The findings revealed that SPMI was implemented through the PPEPP cycle (Planning, Implementation, Evaluation, Control, and Improvement) with KOM serving as the core instrument. The curriculum was developed contextually and collaboratively, forming the foundation for a strong quality culture. The educational output included improved academic and non-academic achievements as well as enhanced administrative order. The outcomes involved institutional transformation, strengthened governance, teacher professionalism, and increased public trust. A sustainable quality culture grew through the active participation of all stakeholders and a well-documented work system. This study concludes that SPMI at MAN 2 Model Medan has become an adaptive, collaborative, and transformative management system in advancing educational quality.